An appraisal of urine cytology in the diagnosis of transitional cell carcinoma of the urinary bladder - Zeki, Tariq Mohamed; Ali, Hussam H.; Hassan, Maha Shakir; Al- Salihi, Anam R.; Hussein, Alaa G. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Urine cytology has an acceptable sensitivity, & specificity that justifies its use in the current diagnostic protocol. In Iraq transitional cell carcinoma (TCC) constitute about 62.1 % of bladder cancer (which ranks the third according to the results of Iraqi Cancer Registry 1995-1997). Urine cytology used in the primary diagnosis, follow up, and in the screening programs of asymptomatic but high-risk patients. Patients and methods: This study was conducted on 93 patients, diagnosed or clinically suspected to have TCC of the urinary bladder attending to the Urological department in ALKadhimiya Teaching Hospital, AL-Yarmouk Teaching Hospital, and Baghdad Medical City. During the period from July 2004to July 2005. 76 were males & 17 were females. Urine cytological examination was done to those patients using two types of stain (hematoxylin and eosin, and papanicoloau stain) to detect malignant cells with the identification of the degree of differentiation, if possible, the cytological findings were correlated with the histopathological findings. And the cytological findings compared regarding each type of stain. Results:. Mean age of the patients was 59 year. Male:female ratio was 4.4:1. Main clinical presentation was hematuria (45.8%) of the total. Urine cytological examination has a sensitivity of 87.7%, specificity of 100% with an overall accuracy of 78% in the detection of TCC of urinary bladder. The main chief complaint of patients with TCC was haematuriawitch constitute 45.8% of the total. The percentage of highgrade cases in urine cytology was higher than that in histopathology.the percentage of cases of TCC diagnosed by papanicoloau stain was more than that diagnosed by H & E (73.24% by pap stain versus 70.42% by H&E). Conclusion: Urine cytology has an acceptable sensitivity, specificity and an overall accuracy in the diagnosis of TCC of urinary bladder, and it offers a good chance for determination of the grade of the tumor especially in high grade tumor. Pap stain was better in the diagnosis of TCC.